Evaluating End-to-End Delay in Road-Based Routing Protocols for VANETs with Snake Optimization - Hanadi Hassan karim Al-Maliki; Hamid AL-Asadi (Wasit Journal of Computer and Mathematics Science)
Vehicular Ad hoc Networks (VANETs) require efficient routing protocols due to their dynamic network  topologies and high mobility. This paper proposes a Road-Based Vehicular Traffic (RBVT), which combines reactive (RBVT-R) and proactive (RBVT-P) routing protocols to improved the performance. We evaluate the impact of RBVT on Average End-to-End Delay (AEED) by comparing it with existing protocols such as AODV, DSR, GPSR, OLSR, DSDV, and WRP. Furthermore, we integrate Snake Optimization Algorithm (SOA) with RBVT to optimize routing and reduce AEED. Simulations demonstrate that SOA-RBVT significantly reduces AEED compared to baseline protocols, especially in dense VANET scenarios.